Cost analysis for the implementation of green roofs in semi-arid region with reuse of gray waters (Research, Society and Development, 2022)
The growing development of civil construction brings the need to adopt constructive and sustainable methods. The implementation of green roofs has shown potential within construction methods. However, one of the obstacles to the implementation of this technique are the regional climatic factors, so this technique has not been widely used in regions with these characteristics. Therefore, this research work addressed a gray water reuse system as an irrigation material for green roofs. The reused water comes from the kitchen and washing machine. The methodology used was a bibliographic research based on published articles, books and periodicals. Furthermore, an implementation cost analysis for a green roof was presented. In this study, a 250 m² residence was analyzed, with 156 m² of green roof with laminar system. For the living roof area in question, the final product in relation to costs was estimated at an average of R$564/m². The value includes the installation, waterproofing of the substrate, the laminar system and the materials used for the greywater reuse system.